Applications of polymerase chain reaction for the detection of equine Leishmania sp. Infection - Escobar, Taiane Acunha; Döwich, Gabriela; Cantele, Leticia Carvalho; Góss, Geórgia Camargo; Porciúncula, Marcelo Lameiro; Leite, Carla Teixeira [UNESP]; Zuravski, Luísa; Duarte, Claudia Acosta; Lübeck, Irina (Universidade Estadual de Londrina, 2020)
Leishmaniasis is a neglected zoonotic disease caused by a variety of pathogenic Leishmania species. In the New World, especially in Brazil, visceral leishmaniasis (VL) is caused by Leishmania infantum. The pathogen can infect several animal species including dogs, foxes, rodents, primates, felines, equines and humans. Dogs act as the primary domestic reservoirs. This study aimed to use polymerase chain reaction (PCR) for detecting Leishmania infection in horses living in a canine visceral leishmaniasis (CVL) endemic region. DNA samples from horse peripheral blood were used to perform PCR. Templates were amplified using primers for the kinetoplast DNA (kDNA) minicircles, which were able to detect different species of Leishmania. In addition, primers for internal transcribed spacer (ITS) of ribosomal DNA were used for detection of Trypanosomatidae sp. Amongst the 75 (39%) positive PCR samples from total 192 samples, 21 samples were positive for kDNA and 63 samples were positive for either ITS, ITS1, or ITS2 gene markers. The kDNA PCR and sequencing allowed the detection of L. infantum in horse blood samples. To our knowledge, this is the first report of equine infection with L. infantum in Southern Brazil. These results proved that L. infantum could also infect horses in addition to humans and dogs, as well as in European countries. This conclusion emphasizes the urgent need to follow up investigation of the infection in these animals.
Keywords: Diagnostic methods; Horses; Infection; Leishmania infantum